Handbook on migration and the family - Waters, Johanna L.; Yeoh, Brenda S. A. (Edward Elgar Publishing, 2023)
"This Handbook is a timely and critical intervention into debates on changing family dynamics in the face of globalization, population migration and uneven mobilities. By capturing the diversity of family 'types', 'arrangements' and 'strategies' across a global setting, the volume highlights how migration is inextricably linked to complex familial relationships, often in supportive and nurturing ways, but also violent and oppressive at other times. Featuring state-of-the-art reviews from leading scholars, the Handbook attends to cross-cutting themes such as gender relations, intergenerational relationships, social inequalities and social mobility. The chapters cover a wide range of subjects, from forced migration and displacement, to expatriatism, labour migration, transnational marriage, education, LGBTQI families, digital technology and mobility regimes. By highlighting the complexity of the migration-family nexus, this Handbook will be a valuable resource for researchers, scholars and students in the fields of human geography, sociology, anthropology and social policy. Policymakers and practitioners working on family relations and gender policy will also benefit from reading this Handbook"--